Perbandingan konsep kendiri staf di bawah kepemimpinan wanita - Mad Shah, Ishak (Penerbit UTM Press, 2007)
An outcome of a work is related with how a person reflects and thinks about himself. Someone who has positive attitude usually produces excellent result from his work. It is because when the person has high self esteem he will be more responsible and he is willing to give full commitment to his job and his organization. Moreover, he will feel comfortable to work with his employees. A recent study, however, found that self–concept of a worker depends on the gender of the employer, Self–concept of female workers and male workers is different from each other. The purpose of this research is to investigate the differences of management staffs self–concept who work under women leadership. This study was carried out in Universiti Teknologi Malaysia and a total of 53 management staffs who work with women employers were randomly selected to be the respondents of the study. This research utilized Tennesse Self–Concept Scale (TSCS) to measure the self–concept. There are five self–concepts have been investigated by using the instrument which are emotion self–concept, social self–concept, moral self–concept, physical self–concept and last but not least personal self–concept. The overall finding of the study indicates that there is no difference between self–concept of women workers and men workers who work under women leadership. menunjukkan bahawa tidak terdapat perbezaan dalam konsep kendiri antara staf pentadbiran wanita dan staf pentadbiran lelaki di bawah pimpinan ketua wanita.